Formation of a Professional teacher`s personality in the classical methodology - Orlov, Valeriy (Professional Pedagogics, 2014)
The author points out that the dimensions of the classical methodology of the individual teacher professional development has always been regarded in the unity of cognition and self-discovery, personal development and professional formation; interdependence and mutual influence of pedagogical phenomena dialectical interaction between the general and the individual, and his whole elements of social and individual values. The leading ideas of becoming a professional individual teacher were to remain conceptual provisions regarding the objective (social) and subjective (personal) determination of the nature and life of the individual in question in the philosophy of G. Hegel, I. Kant, N. Berdyaev, V. Frankl, the phenomenological reflections E. Husserl, G. Ingarden, A. Camus, A. Loseva, M. Heidegger et al., in the works of G.Skovoroda, P. Yurkevych, V. Vernadsky on the nature of the human person, of her spirituality , formation outlook, attitude to work reality in the classics Ukrainian Education – K Ushinskiy, A. Makarenko, V. Sukhomlynsky, which confirms the idea of high spiritual teacher training and professional pedagogical culture, humanist, creative personality, able to transform themselves and the world.The main emphasis in the article on the need to preserve the best traditions of pedagogy. It is emphasized that in search of innovation is important not to lose the position of humanism,lyudynotsentryzmu, kulturovidpovidnosti, national identity. The need to remember that teacher yesterday, today and always - a person who realizes the professional responsibility, «openly» with the declared meaning outside of their own actions, is your personal sense of professional activities, guided him taking responsibility for its results, and their professional success sees the success of their students.
Keywords: personality teacher; professional development; classical methodology; phenomenology; education formation; education development; professional education; professional culture; existential freedom; professional responsibility